Antecedents of the use of social media and its effects on startups’ resilience and innovation - Giordani, Mikaéli da Silva; Schlup, Daiani; Beuren, Ilse Maria (REGEPE Entrepreneurship and Small Business Journal, 2023)
Objective of the study: Examine which antecedent factors favored the use of social media and which, substantiated in the organizational resilience, provoked innovation in startups in times of pandemic. Methodology/approach: A survey was carried out on startups located in the South and Southeast regions of Brazil, listed on the StartupBase, obtaining 119 questionnaires answered by the managers. Structural equation modeling was used for the analysis of the hypotheses. Main results: The environment, measured by external pressure, and the organizational, measured by the dimensions of internal readiness and strategic benefits, figure as antecedents of the use of social media. The use of social media has a direct and positive effect on organizational resilience and, mediated by organizational resilience, has positive effect on innovation. Theoretical/methodological contributions: The literature is expanded by analyzing antecedents and consequences of the use of social media, particularly related to the capacity for organizational resilience and the promotion of innovation. Relevance/originality: Empirical evidence indicates that social media can help develop resilience in startups and, consequently, promote innovation in times of pandemic. Social/management contributions: The focus on social media revealed that it can generate benefits in periods of restrictions, since the use of social media substantiated in organizational resilience enables interaction and value creation.